An Integrated Stratigraphic Approach to Investigating Evidence of Paleoearthquakes in Lake Deposits of Eastern Canada - Brooks, Gregory (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2015)
SUMMARY Seismic shaking can generate mass movements, turbidites, and soft-sediment deformation within lake basins. These ‘disturbed’ deposits may be preserved, and provide a stratigraphic record of paleoearthquakes. A three-dimensional seismostratigraphy of the lake deposits can be constructed from a high-density, sub-bottom acoustic profile (SAP) survey, allowing disturbed deposits within the basin to be identified and mapped. Event layers composed of one or more disturbed deposits can be identified within the seismo-stratigraphy, and targeted coring of the lake deposits provides ground-truthing of the disturbed deposits. Analysis of organic or sediment materials sampled from recovered cores allow ages to be assigned to the event layers. Maps depicting the distribution, extent and types of disturbed deposits within each event layer can be compiled by integrating the event layer stratigraphy and the three-dimensional architecture of the lake deposits. An intrabasin, multi-deposit event layer is the likely signature of significant past earthquake shaking, but possible non-seismic triggers also need to be assessed. An earthquake catalogue spanning 16 000 years for central Switzerland exemplifies the results of an integrated seismo- and chrono-stratigraphic approach to paleoseismic investigation. This approach to the investigation of eastern Canadian lake basin(s) has the potential to significantly augment the eastern Canadian earthquake catalogue. Conversely, the absence of seismically-induced disturbed deposits in SAP profiles and in lake core within a given area can help establish negative evidence of paleoseismicity.